Clinical manifestations and genetic analysis of a newborn with Arboleda−Tham syndrome - Zeng, Feng; Yang, Yue; Xu, Zhaohui; Wang, Ziwen; Ke, Huan; Zhang, Jianhong; Dong, Tongtong; Yang, Wenming; Wang, Jiuxiang (Frontiers in Genetics, 2022)
Abstract Arboleda-Tham syndrome (ARTHS) is a rare disorder first characterized in 2015 and is caused by mutations in lysine (K) acetyltransferase 6A (KAT6A, a.k.a. MOZ, MYST3). Clinical symptoms have rarely been reported in newborns from birth during the first few months after birth. In this study, the newborn was diagnosed with ARTHS based on clinical symptoms and had a de novo mutation c.3937G>A (p.Asp1313Asn) in KAT6A. the clinical manifestations, diagnosis, and treatment of a newborn with ARTHS were recorded during follow-up observations. The main symptoms of the proband at birth were asphyxia, involuntary breathing, low muscle tone, early feeding, movement difficulties, weak crying, weakened muscle tone of the limbs, and embrace reflex, facial features were not obvious at birth. There was obvious developmental delay and intellectual disability, as well as hypotonic and oro-intestinal problems in the first few months after birth. Mouse growth factor was used to nourish brain nerves, touching, kneading the back, passive movement of limbs, audio-visual stimulation was used to rehabilitation. We hope this study expanded the phenotypic spectrum of this syndrome to newborns and the library of KAT6A mutations that lead to ARTHS. Consequently, the data can be used as a basis for genetic counseling and clinical and prenatal diagnosis for ARTHS prevention.